Geochemical characteristics of gases associated with natural gas hydrate - Li, Yuanyuan; Chang, Jingyi; Lu, Hailong (Frontiers in Marine Science, 2022)
With more natural gas hydrate samples recovered and more research approaches applied to hydrate-bound gas studies, data concerning the geochemical characteristics of hydrate-bound gases have been increased significantly in the past decades. However, a systematic summary of these studies is not available, yet. In this study, the data published about the geochemistry of gas bounded in natural hydrate are compiled, and subsequently the primary origin and the post-generation secondary process of the gases are discussed, for better understanding of the formation process of natural gas hydrate. The primary origins of hydrate-bound gases can be divided into biogenic and abiogenic gas in a broad classification scheme on whether organic matters are involved, in which biogenic gas is controlled by the type, sapropelic or humic, and maturity, from immature, mature to over-mature, of organic matter, whereas abiogenic gas is found mainly associated with inorganic reactions such as high-temperature magmatic processes and gas-water-rock reactions. Apart from primary origins, secondary processes after gas generation such as migration, mixing, biodegradation and oxidation occur during the migration and/or storage of gases can significantly alter their primary features. Conventional methods such as stable isotope and molecular ratios are basic proxies, which have been widely adopted to identify these primary origins and secondary processes. Isotopic compositions of C2+ gases have been employed to identify the precursor of the gases or source rocks in recent years. Data from novel techniques such as methane clumped isotope and noble gases bring additional insights into the gas origins and sources by providing information about the formation temperature of methane or proxies of mantle contribution. A combination of these multiple geochemical approaches can help to ascertain an accurate delineation of the generation and accumulation processes of gases in a gas hydrate reservoir.